Protein C and antithrombin III in children with acute leukemia - Atlıhan, Füsun; Karakaş, Zeynep; Batun, Sabri (The Turkish Journal of Pediatrics, 1993)
In this study Protein C (PC) and antithrombin III (AT III) levels in childhood acute leukemia were investigated. The mean PC activity levels in 19 newly diagnosed cases of acute leukemia were significantly lower as compared with the normal controls (p < 0.05). A significant increase was found (p < 0.01) in the patients in remission. Prior to treatment 78.8 percent of patients had decreased PC activity levels, but all patients had normal PC activity during remission. Decreased PC activity levels were found to be independent of the leukocyte count and liver function. No statistically significant difference was found in the AT III antigen levels between the untreated patients, the patients in remission and the control group. Our results indicate that apart from thrombocytopenia, low PC activity levels and alterations in fibrinolysis and coagulation may be responsible for the hemorrhagic manifestations observed in cases of acute leukemia.